Digitization of Employee Attendance Processes Through a Web-Based QR Code System at MA Nurul Wahid al Wahyuni - Karim, Abdul; Hidayah, Moh. Syahrul; Adom, Nazri (Journal of Electrical Engineering and Computer (JEECOM), 2025)
The manual attendance process at MA Nurul Wahid al Wahyuni often causes various problems, such as late recording, inaccurate data, and potential fraud. Therefore, this study aims to design and implement a web-based employee attendance system by utilizing QR Code technology as a more efficient and accurate digital solution. The methodology used in developing this system is the Waterfall method, which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. This system allows each employee to take attendance by scanning a QR Code via a mobile device, which automatically records the time and user identity into the database. The test results show that this system is able to increase the efficiency and accuracy of attendance recording, namely this system is proven to be able to speed up the attendance process and cannot be changed by ordinary users, as well as facilitate the management of attendance data by the administration department. With the implementation of this system, it is expected that the attendance process at MA Nurul Wahid al Wahyuni will become more modern, transparent, and integrated